Mulinum ulicinum (Azorelloideae, Apiaceae), nueva cita para Chile - FERNÁNDEZ, MARTINA; EZCURRA, CECILIA; CALVIÑO, CAROLINA I. (Gayana Botánica, 2014)
Mulinum ulicinum is recorded for the first time in Chile. This species and M. crassifolium are the only two species of the genus growing in the Region of Antofagasta. A description and illustration of M. ulicinum is provided, as well as a key to differentiate it from M. crassifolium.